Innovative integrated system for real-time measurement of hybridization and melting on standard format microarrays. (June 2008) - Marcy, Yann; Cousin, Pierre-Yves; Rattier, Maxime; Cerovic, Gordana; Escalier, Guilhem; Béna, Gilles; Guéron, Maurice; McDonagh, Lorcan; le Boulaire, Françoise; Bénisty, Henri; Weisbuch, Claude; Avarre, Jean-Christophe
Despite the great popularity and potential of microarrays, their use for research and clinical applications is still hampered by lengthy and costly design and optimization processes, mainly because the technology relies on the end point measurement of hybridization. Thus, the ability to monitor many hybridization events on a standard microarray slide in real time would greatly expand the use and benefit of this technology, as it would give access to better prediction of probe performance and improved optimization of hybridization parameters. Although real-time hybridization and thermal denaturation measurements have been reported, a complete walk-away system compatible with the standard format of microarrays is still unavailable. To address this issue, we have designed a biochip tool that combines a hybridization station with active mixing capability and temperature control together with a fluorescence reader in a single compact benchtop instrument. This integrated live hybridization machine (LHM) allows measuring in real time the hybridization of target DNA to thousands of probes simultaneously and provides excellent levels of detection and superior sequence discrimination. Here we show on an environmental single nucleotide polymorphism (SNP) model system that the LHM enables a variety of experiments unachievable with conventional biochip tools.